PENGARUH EXPERIENCE QUALITY TERHADAP CUSTOMER LOYALTY DENGAN PERCEIVED VALUE DAN BRAND IMAGE SEBAGAI VARIABEL INTERVENING DI DE SOEMATRA 1910 SURABAYA - Meyer Fossetta Hansory; Diah Dharmayanti (Institute of Research and Community Outreach - Petra Christian University, 2014)
The growth of the upper class society in Indonesia has increased, especially in the second largest metropolitan city of Surabaya. In Surabaya, there is a function house where to understand the way of thinking of its customer and the target are the upper class society in Surabaya. This research aims to analyze the influence of Experience Quality (accessibility, competence, customer recognition, helpfulness, personalization, problem solving, promise fullfilment, value for time) on Customer Loyalty by considering the factors of Perceived Value (instrumental value, the expressive value, hedonistic values, sacrifice value) and Brand Image (mystery, sensuality, intimacy). This study conducted by distributing questionnaires to 120 respondents who are the consumers of De Soematra 1910. Analysis technique used is of quantitative analysis with path analysis method